Concordance of immunohistochemistry between core needle biopsy and surgical resection of breast cancer - (:unkn) unknown (My University, 2017)
0

Background/aim: The purpose of this study was to evaluate the concordance of immunohistochemical (IHC) parameters of breast lesions between the core needle biopsy (CNB) and the surgical resection specimen. Materials and methods: CNB and resection specimens of female patients were retrospectively analyzed. ER, PR, HER-2, and Ki-67 parameters were compared for each patient. A total of 284 cases were assessed. Forty-one and 48 cases were excluded from the HER-2 and Ki-67 examinations, respectively, because the CNBs did not allow for IHC. Results: Concordance rates were 93.3% for ER, 89.4% for PR, 90.1% for HER-2, and 80.9% for Ki-67. Conclusion: CNB is accurate for the evaluation of the surrogate molecular profile of invasive breast cancer despite the heterogeneity of tumors.
Keywords: Cerrahi